An Online, Modular Curriculum Enhances Surgical Education and Improves Learning Outcomes in East, Central, and Southern Africa: A Mixed-Methods Study. Issue 1 (2nd March 2022) - Parker, Andrea S.; Steffes, Bruce C.; Hill, Katherine; Bachheta, Niraj; Mangaoang, Deirdre; Mwachiro, Michael; Torbeck, Laura; White, Russell E.; Bekele, Abebe; Parker, Robert K.
Abstract : Objective: We aimed to determine the impact of a standardized curriculum on learning outcomes for surgical trainees in East, Central, and Southern Africa (ECSA). Background: As surgical education expands throughout ECSA, there is a recognized need for a standardized curriculum. We previously described the design of a novel, large-scale, flipped-classroom, surgical curriculum for trainees in ECSA. Methods: In January 2020, the first year of curricular content for trainees of the College of Surgeons of ECSA was released, containing 11 monthly thematic topics, each with 2 to 5 weekly modular subtopics. We aimed to evaluate 3 outcomes utilizing data sources incorporated into the curriculum structure. Learner engagement was assessed by the number of trainees completing curriculum topics. User experience was evaluated using quantitative and qualitative feedback responses to embedded surveys for each content week. Curriculum impact on trainee examination performance was assessed by comparing certification examination scores stratified by the number of curricular topics each trainee completed. Results: Two hundred seventy-one trainees (96%) in 17 countries accessed at least 1 weekly module. Trainees completed a median of 9 topics (interquartile range: 6–10). The feedback survey response rate was 92% (5742/6233). Quantitative and qualitative responses were positive in overall module value (93.7% + 2.6%), amount of learning experienced (97.9% + 1.4%), confidence in achieving learning objectives (97.1% + 2.4%), and ease of use of the module (77.6% + 5.98%). Topic-related certification examination performance improved significantly with increased completion of thematic topics. Conclusions: A standardized surgical curriculum in ECSA demonstrated excellent trainee usage, positive feedback, and improved examination scores.